Manajemen Strategik Rekrutmen Dalam Meningkatkan Kuantitas Jemaah Haji dan Umrah (Studi Kasus Pada KBIHU Al-Magfiroh) - Fitri, Agnia Nurul; Solahudin, Dindin; Fitriani, Putri Diesy (Mabrur: Academic Journal of Hajj and Umra, 2024)
The purpose of this research is to explore the strategic implementation process, and the results of recruitment by KBIHU Al-Magfiroh in order to increase the quantity of Hajj and Umrah pilgrims. With a qualitative approach, this research is organized descriptively to describe the data related to the problems to be discussed. Strategic management theory in this study aims to be able to design effective and efficient implementation. The results of this study, The process of registering prospective pilgrims at KBIHU Al-Magfiroh implements a good recruitment strategy program. The implementation of the management strategy used by KBIHU Al- Magfiroh in recruiting its pilgrims uses internal and external strategies in achieving maximum results. The results of the pilgrimage recruitment strategy at KBIHU Al-Magfiroh are effective and efficient.